ASPEK MASKULINITAS PADA PERKEMBANGAN SISTEM KEPERCAYAAN POLITEISME DAN MONOTEISME - Rilliandi Arindra Putawa (Sanjiwani: Jurnal Filsafat, 2023)
This study aims to explore aspects of gender, especially masculinity which can often be found in the concept of divinity. This research is qualitative research with a literature study data collection technique that aims to compare the effect of these aspects of masculinity on two types of belief systems, namely polytheism and monotheism. This research will limit the belief system that is known in Indonesia. From the search that has been carried out on these samples, it was found that there is a correlation between the more precise description of God and the human aspect, which makes it easier to find the human aspect. This is more common in polytheistic belief systems than monotheism. The problem of masculinity will be even more complicated if there is the concept of God's incarnation in human form in the monotheistic belief system, which then leads to the increasingly strong influence of masculinity on that belief system.